Impact of carbon impurities on the initial leakage current of AlGaN/GaN high electron mobility transistors - Gao, Yu (2019)
We have systematically studied the origin of high gate-leakage currents in AlGaN/GaN high electron mobility transistors (HEMTs). Devices that initially had a low gate-leakage current (good devices) are compared with ones that had a high gate-leakage current (bad devices). The apparent zero-bias Schottky barrier height of bad devices (0.4 < ϕB0 < 0.62 eV) was found to be lower than that of the good devices (ϕB0 = 0.79 eV). From transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) analysis, we found that this difference is due to the presence of carbon impurities in the nickel layer in the gate region.